Teachers' conflicting responses to change: an evaluation of the implementation of senior social studies for the NCEA, 2002-2006 : a thesis presented in partial fulfilment of the degree of Doctor of Education (EdD), Massey University, Palmerston North, New Zealand - Taylor, Rowena Margaret (Massey University, 2008)
The thesis provides a socio-historical perspective through which to evaluate the first five years of implementation (2002 to 2006) of social studies within the National Certificate of Educational Achievement [NCEA] in New Zealand secondary schools. The experiences of both lead educators, with responsibilities at a national level, and classroom teachers provide insights into the personal, contextual and institutional factors which have enabled and constrained the implementation process, especially at NCEA level one. The inclusion of social studies as a subject for the new qualifications and assessment system in New Zealand, the NCEA, heralded a significant opportunity for this integrated subject to gain academic status and acquire a unique identity within the senior secondary school curriculum. Paradoxically it set a relatively strongly framed assessment system beside a curriculum that has traditionally been weakly classified and framed (Bernstein, 1971). This paradox has created tensions for teachers who have responded in different ways, from full implementation to a more functional approach. Two groups of teachers were identified in the course of this study. The idealists are passionate advocates for senior social studies and are likely to implement it to all three NCEA levels in their school. The pragmatists, on the other hand, are more likely to offer only level one social studies, typically to their more academically able year 10 (Form 4) students for extension purposes, and also to induct them into the assessment requirements of the NCEA system before they study the traditional social science subjects at levels one, two and three. This pragmatic approach reflects past practices of the pre- NCEA, School Certificate era (1945-2001). It continues to reinforce the low status and unclear identity of senior social studies within the social sciences as well as within an already overcrowded senior school curriculum. At the end of this first five year period of implementation the viability of senior social studies is at a critical juncture, with its on-going success not yet assured.
Keywords: National Certificate of Educational Achievement; New Zealand secondary schools; Teachers' attitudes; Social sciences; Fields of Research::330000 Education::330200 Curriculum Studies